Possibilities of reconstruction and implant-prosthetic rehabilitation following mandible resection - Konstantinović Vitomir S.; Todorović Vladimir S.; Lazić Vojkan M. (Vojnosanitetski Pregled)
Introduction. Mandible reconstruction is still very challenging for surgeons. Mandible defects could be the consequence of ablative surgery for malignancies, huge jaw cysts, infection and trauma. Segmental resection of the mandible may compromise orofacial function and often lead to patients psychological disorders. Despite very frequent use of microvascular flaps, autogenous bone grafts are still very reliable technique for mandible reconstruction. Comprehensive therapy means not only mandible reconstruction, but prosthodontic rehabilitation supported by dental implants, which can significantly improve patients quality of life. The aim of this paper was to evaluate possible techniques of mandible reconstruction and to present a patient who had been submitted to mandible resection and reconstruction with autogenous iliac bone graft and prosthodontic rehabilitation with fixed denture anchoraged by disc-shaped implants in early loading protocol. Case report. Mandible reconstruction was performed simultaneously with resection. Autogenous iliac bone graft was taken, reshaped and placed in two parts, to the required optimal contour of the mandible. After graft consolidation, decision was made for prosthodontics rehabilitation with fixed dentures supported by implants. In addition to the standard preoperative procedures, planning was done based on a biomodel gained by rapid prototyping after CT scan. It offered a real 3D planning to obtain a proper shape, dimension and the position of implants. Conclusion. If bone dimensions of a reconstructed mandible are insufficient, like in the presented case, the use of basal osseointegrated implants may be a method of choice. Avoiding bone augmentation procedures, as well as early loading protocol for this type of implants, shorten the total rehabilitation time, which is very convenient for patients. Fixed denture supported by dental implants is the best solution for comprehensive rehabilitation after mandible resection. [Projekat Ministarstva nauke Republike Srbije, br. 175075]